Activities of Three Erythrocyte Enzymes of Hyperglycemic Rats (Rattus norvegicus) Treated with Allium sativa Extract. - P.C, Chikezie; A.A, Uwakwe (Pharmacognosy Communications)
Background/Objective: The present study sought to investigate erythrocyte glutathione S-transferases (GST), NADH-Methaemoglobin reductase (NADH-MR) and Na+/K+-ATPase activities of hypoglycemic rats treated with ethanol/water (1:2 v/v) extract of A. sativa as an agent of glycemic control. Materials and Methods: Hyperglycemia was induced by a single intra-peritoneal injection of 0.1 mol/L alloxan monohydrate in phosphate buffer saline (PBS) solution (pH =7.4); dosage = 140 mg/kg. At the end of the experimental time (t = 76 h), erythrocyte GST, NADH-MR and Na+/K+-ATPase activities as well as serum fasting blood sugar (FBS) levels were measured by spectrophotometric methods. Results: Serum FBS levels of control/normal (C/N) rats ranged between 72.93±0.82– 95.12±0.92 mg/dL, whereas experimental rats without glycemic control gave: 249.41±1.03–256.11±1.23 mg/ dL. Hyperglycemic rats treated with ethanol/water (1:2 v/v) extract of A. sativa exhibited comparative reduced serum levels of FBS alongside with erythrocyte GST, NADH-MR and Na+/K+-ATPase activities. The average relative activities of the three enzymes and corresponding order of enzyme activity in hyperglycemic rats treated with ethanol/water (1:2 v/v) extract of A. sativa was: NADH-MR = 60.99% > GST = 47.81% > Na+/K+-ATPase = 46.81%. In the same order, relative activities of the three enzymes in rats without glycemic control were: NADHMR = 49.65% > GST = 23.69% > Na+/K+-ATPase = 17.02%. Conclusion: Erythrocyte GST, NADH-MR and Na+/K+-ATPase activities gave insights into the pathophysiology of the diabetic state and served as biomarkers for ascertaining therapeutic control in Type 1 diabetes mellitus.
Keywords: Glutathione S-transferases; NADH-Methaemoglobin reductase; Na+/K+-ATPase; Allium sativa; hyperglycemia; diabetes mellitus